Stakeholders’ views on the utility and employment strategies of clinical associates - Arthur Setlhapelo; Jacqueline E. Wolvaardt (South African Family Practice)
Background: Clinical associates (ClinAs) were introduced into the South African healthcare system to increase the numbers of skilled health professionals. Little is known on how they are viewed. This study explored stakeholder views on the utility and employment strategies of ClinAs in the public sector.